SISTEM APLIKASI MANAJEMEN DATA VENDOR PADA PT. KALBE FARMA – CIKARANG - Komalasari, Yuli; Ukhrowi, Azzarnuji Nur; Adawia, Popon Rabia; Chalimatusadiah, Chalimatusadiah (Journal of Information System, Informatics and Computing, 2025)
In the digital era, fast and open access to information is the key to an organization's success. PT Kalbe Farma, as a leading pharmaceutical company, faces obstacles in providing access to information related to vendor data and employee training. This limitation has an impact on the company's operational efficiency and decision making. Vendors are important business partners in the availability of goods. The right steps are needed in selecting a Vendor so that activities in a company run smoothly. To overcome this problem, a "Vendor Data Management System at PT Kalbe Farma Cikarang" was designed. The design uses the Rapid Application Development (RAD) method, which is a system that can be used quickly and is reusable. RAD is also a system with high dynamism. This system aims to further explain to Employees about Vendors, Vendor needs and the Vendor Data Management System that can open up access to vendor information that is easily known by Employees. This system also helps to see Vendor data performance, whether the Vendor is worthy of continuing cooperation. In addition, this system allows companies to respond more quickly to training needs, so that employee performance can improve. The trial results show that this system is effective in improving information accessibility, optimizing the training process, and increasing the efficiency and productivity of the company. With proper implementation, this system contributes significantly to the improvement of the company's overall operations and competitiveness